O Intelectual Americano de Ralph Waldo Emerson - Oliveira (trad.), Daniela; Rosas (trad.), Vítor; Dias (trad.), Leonora; Pires (rev.), Carla Morais (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2020)
.